2002
DOI: 10.1086/339807
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Acute Viral Gastroenteritis in Children Hospitalized in Rouen, France

Abstract: This study assessed the epidemiologic characteristics of acute viral gastroenteritis in hospitalized children. A stool sample obtained from each child was analyzed for the presence of astrovirus, calicivirus, rotavirus, adenovirus, enterovirus, and digestive bacteria. Of the 438 stool samples obtained, 138 tested positive for > or =1 pathogen during the winters of 1997-1998 and 1998-1999 (P<.001). Virologic tests revealed rotavirus in 17.3% of samples, calicivirus in 7.3%, astrovirus in 6.8%, adenovirus in 0.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
35
4
7

Year Published

2002
2002
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(64 citation statements)
references
References 70 publications
18
35
4
7
Order By: Relevance
“…For children younger than 2 years, no significant differences were observed between RV and NoV infections or between these and other virus infections with regard to the severity of the symptoms (P Ͼ 0.05). Although a study conducted in Vietnam (25) also found similar rates of severity of RV and NoV infections, this result is in contradiction to most of the previous work carried out in developed countries (6,9,23,24,31), which found lower levels of disease severity with NoVs. In the present study, the delay to hospitalization for NoV-infected children and the lack of medical (9) showed conflicting results between the severity scoring and the degree of dehydration.…”
Section: Discussioncontrasting
confidence: 82%
“…For children younger than 2 years, no significant differences were observed between RV and NoV infections or between these and other virus infections with regard to the severity of the symptoms (P Ͼ 0.05). Although a study conducted in Vietnam (25) also found similar rates of severity of RV and NoV infections, this result is in contradiction to most of the previous work carried out in developed countries (6,9,23,24,31), which found lower levels of disease severity with NoVs. In the present study, the delay to hospitalization for NoV-infected children and the lack of medical (9) showed conflicting results between the severity scoring and the degree of dehydration.…”
Section: Discussioncontrasting
confidence: 82%
“…The literature concerning symptom severity in norovirus and rotavirus gastroenteritis is heterogeneous [42]. A number of previous studies found lower levels of disease severity in norovirus than in rotavirus gastroenteritis, and most of these were carried out in developed countries [7,[43][44][45][46][47]. In contrast, other studies found no significant differences between the severity of rotavirus and norovirus infections [48][49][50][51].…”
Section: Discussionmentioning
confidence: 99%
“…Although HuCV is emerging as a cause of sporadic gastroenteritis as a sole pathogen in young children, there are not many data about the incidence of this viral infection. During previous studies in other countries, this infection was detected in 3.5 to 20% of sporadic cases among young children (1,2,5,9,10,12,14,15,16,22,24). To date, there is to our knowledge a lack of data from Spain.…”
mentioning
confidence: 85%